Perilaku Sadfishing pada Aplikasi TikTok dan Penanganannya: Studi Kasus pada Siswa SMA - Alatas, Balqis Sayidina; Harum, Akhmad; Fitriana, Fitriana (Universitas Sebelas Maret, 2025)
This qualitative clinical case study examines the manifestations, causal factors, and management strategies associated with sadfishing behavior in a student. Data were collected through interviews, observation, and documentation, and analyzed using qualitative descriptive methods. The study addressed three primary objectives: describing the behavior, identifying its causes, and detailing the intervention process. Results indicated that RR's sadfishing involved repeatedly re-posting sad content online as a maladaptive strategy to alleviate emotional distress and seek validation for unexpressed suffering. The identified causes included internal factors, such as an inner conflict between the desire for relief and difficulty communicating, reinforced by social withdrawal, as well as external factors, including limited social support from family and insufficient awareness among school staff and peers. The main intervention applied was the Cognitive Restructuring technique. Following the intervention, the subject demonstrated a gradual reduction in sadfishing behaviors and irrational thoughts, along with improved communication skills, reflecting positive changes in emotional regulation, behavior, and mindset.